Godfrey of Bouillon - John, Simon (Simon A.), author.
1 online resource (284 pages)
Keywords: This book offers a new appraisal of the ancestry and career of Godfrey of Bouillon (c.1060-1100), a leading participant in the First Crusade (1096-99), and the first ruler of Latin Jerusalem (1099-1100), the polity established by the crusaders after they captured the Holy City. While previous studies of Godfrey's life have tended to focus on his career from the point at which he joined the crusade, this book adopts a more holistic approach, situating his involvement in the expedition in the light of the careers of his ancestors and his own activities in Lotharingia, the westernmost part of the kingdom of Germany. The findings of this enquiry shed new light on the repercussions of a range of critical developments in Latin Christendom in the eleventh and early twelfth centuries, including the impact of the `Investiture Conflict' in Lotharingia, the response to the call for the First Crusade in Germany, Godfrey's influence upon the course of the crusade, his role in its leadership, and his activities during the initial phases of Latin settlement in the Holy Land in its aftermath.